Well-being among boarding school students: Academic self-efficacy and peer attachment as predictors - Mudzkiyyah, Lainatul; Wahib, Abdul; Bulut, Sefa (Psikohumaniora: Jurnal Penelitian Psikologi, 2022)
Students in Indonesian boarding schools (pondok pesantren) have longer study hours than those in non-boarding schools. They also interact with the same friends all day. This situation makes them vulnerable to boredom and depression, and they also run the risk of being bullied. Therefore, student well-being in boarding schools needs to be studied further, with peer attachment and academic self-efficacy as predictors. This study aims to examine the effect of peer attachment and academic self-efficacy on the well-being of students attending boarding school. The study uses a quantitative approach with the linear regression method. It involves 284 students at Madrasah Tsanawiyah (Islamic Junior High School), aged between 13-15 years old, selected using the stratified random sampling method. The data collection instruments employed were the Peer Attachment Scale, Academic Self-efficacy Scale, and School Well-being Scale. The result shows that peer attachment and academic self-efficacy significantly affect school well-being (p < .01, F = 156.181, effective contribution of predictors = 52.3%). It indicates that peer attachment and academic self-efficacy simultaneously significantly influence well-being among students in boarding schools. Students should improve their peer attachment and increase their academic self-efficacy to live well in boarding schools.